Positive Views on Scientific Work Contributed to the Development of Metrology by the Great Scientists of Central Asia - Axmatov, Nemat (European Journal of Life Safety and Stability (2660-9630), 2022)
It is known that in the Middle Ages in Central Asia, scientists of world renown made their contribution to the development of science, including the development of metrology. In addition to being a great astronomer, mathematician, geographer and engineer who lived in 797-861 with melodic calculation, the great scientist Ahmed al-Fargani made a great contribution to the development of metrology.